Terselip Makna Mendalam: Eksplorasi Pantun Buka Palang Pintu Tradisi Perkawinan Masyarakat Melayu Riau (Daerah Pelalawan, Siak dan sekitarnya) - Agung Danuarta; Arum Fajar Rahmawati; Eka Puspita Rini; Nur Azila; Rahmatuljannah Rahmatuljannah; Herlinda Herlinda (Journal of Creative Student Research, 2024)
This research explores the meaning of pantun in the “Buka Palang Pintu” ceremony in the marriage tradition of the Riau Malay community, especially in Pelalawan, Siak and surrounding areas. The pantun used in this ceremony is not just a means of entertainment, but also loaded with deep meaning that reflects the cultural values, customs, and philosophy of life of the local community using a literature review approach and the first step taken is to conduct a comprehensive literature review on the Exploration of Pantun Buka Palang Pintu Marriage Tradition of the Malay Community of Riau. This research shows that rhymes in the “Buka Palang Pintu” ceremony have an important role in building harmonious relationships between the groom and the bride, as well as conveying advice and moral values.